Randomised crossover trial of different postural interventions on bradycardia and intermittent hypoxia in preterm infants. Issue 4 (19th February 2008) - Reher, C; Kuny, K D; Pantalitschka, T; Urschitz, M S; Poets, C F
Abstract : Background: Apnoea of prematurity has been shown to respond to changes in posture. Objective: To investigate the effect of three postural interventions on the rate of bradycardia and desaturation events. Methods: 18 infants (⩽32 weeks' gestational age; 11 boys) with apnoea of prematurity underwent recordings of breathing movements, electrocardiogram and instantaneous heart rate, pulse oximeter saturation (SpO2 ), photoplethysmographic waveforms and digital video frame while in one of three different prone positions. The following interventions were applied in random order: horizontal position (HP), 15° head-up tilt position (TP) and three-level position (3P) according to Kinaesthetics Infant Handling. The primary study variable was the combined event rate of desaturations (SpO2 <85%) and bradycardias (heart rate <80 bpm). One secondary study variable was the duration of body movements. Results: The median (range) combined event rate was 26.7/h (0.3–72.7) in HP, 25.2/h (0.3–70.5) in TP and 21.2/h (0–66.3) in 3P (p>0.05). The median (range) duration of body movements was 10.8 s/h (0–48.2) in HP, 7.1 s/h (0–72.4) in TP and 7.0 s/h (0–47.7) in 3P (p>0.05). Conclusions: No significant advantage of a head-up tilt or a three-level position over a standard horizontal position could be confirmed.